Factors Affecting Farmer’s Decision to Adopt Climate-Smart Agriculture Technologies and Practices in a Climate Smart Village: The Case of My Loi Village, Ha Tinh Province, Vietnam - Ferrer, Alice Joan G.; Le, Ha Thanh (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The study focused on the adoption of 17 CCAFS-introduced Climate Smart Agriculture Technology and Practices (CSA T & Ps) among farmers in My Loi village, Ha Tinh province, Viet Nam. Specifically, the study identified the factors influencing farmer’s decision to adopt CSA T & Ps. Primary data from 215 farmers were collected through face-to-face interviews in September 2021. Results showed that 159 farmers have adopted at least one CSA T & Ps since 2014. Currently, they have adopted four CSA T & Ps, on average. Using logit regression, the factors identified to significantly and positively influence the ever adopt behavior of farmers were attendance to any training on CSA T & Ps, having a fellow farmer as source of information, growing rice, own farmer’s experience as a source of information, and number of crops grown. On the other hand, the two factors that significantly and negatively influence adoption were having men in the family in the labor force and membership in farming organization. Using ordinary least squares, the factors identified to significantly and positively influence intensity or continuous adoption were attendance to any CSA T & Ps training, the agriculture extension officer as source of information, TV as a source of information, positive attitude of looking for better ways of farming, owns farmland, and number of crops grown. Significant but negatively influencing the decision to continuously adopt was having a male family member in the labor force and also ease in finding farm labor. The results highlight the importance of 1) training given for CSA T & Ps; 2). “champion farmers” that can promote new ways of farming; 3) well-informed and highly-skilled agricultural extension officer; 4) having TV at home; 5) favorable attitude of the farmer; 6) ownership of land and growing rice; and 7) number of crops grown. However, having more men family members in the labor force negatively influences adoption behavior. In the context of My Loi, this is understandable because men leave temporarily or permanently the village for work elsewhere. This suggests that farming in My Loi is a space and time for women.